2011
DOI: 10.1179/2045772311y.0000000037
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to community participation among youth with spinal cord injury

Abstract: Youth from small towns, those injured younger, those with incomplete injuries, and those experiencing recent medical complications may need additional supports and resources to maximize participation. Clinicians should work with caregivers to identify and problem-solve obstacles to youth participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…This, in turn, may lead to overcoming obstacles, such as car transfers, uneven terrains and curbs encountered during community mobility with a wheelchair. This made it more likely for these participants to be involved in community activities (Gorzkowski et al 2011 ), thus improving their QoL (Ulrich et al 2012 ). This finding is similar to that of studies conducted by Gorgey ( 2014 ), Mackie, McCormack and Campbell ( 1989 ), Rauch et al ( 2013 ), Thompson ( 2003 ) and Widman et al ( 2007 ) who found that endurance and good upper limb strength are essential for PWSCI to improve mobility and QoL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This, in turn, may lead to overcoming obstacles, such as car transfers, uneven terrains and curbs encountered during community mobility with a wheelchair. This made it more likely for these participants to be involved in community activities (Gorzkowski et al 2011 ), thus improving their QoL (Ulrich et al 2012 ). This finding is similar to that of studies conducted by Gorgey ( 2014 ), Mackie, McCormack and Campbell ( 1989 ), Rauch et al ( 2013 ), Thompson ( 2003 ) and Widman et al ( 2007 ) who found that endurance and good upper limb strength are essential for PWSCI to improve mobility and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The participants who reported lower levels of exertion after the 6MPT tended to be more satisfied with their community participation. This increased satisfaction with community participation may be because of the fact that participants who experienced lower levels of exertion have better endurance, which makes mobilising in the community easier compared to participants with lower endurance, leading to higher levels of community participation (Gorzkowski et al 2011 ). This adds to the above statement on distances pushed during the 6MPT, that good endurance is a major factor in improving community mobility and independence in PWSCI (Mackie et al 1989 ; Widman et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As participation in travel-related activities has the potential to make meaningful improvements in the lives of people with SCI, it is critical to look at the process of participation and how its various antecedents affect the process. Although not specific to participation in travel, the literature offers a plethora of studies that have identified factors influencing participation, including individuals’ physical conditions of poor health or pain (Alexander et al, 2009) and injury characteristics (Burnett & Baker, 2001; Waters et al, 1998); demographic factors such as age, female gender, minority race, lower income, and lower education level (Kader et al, 2018; Krause, 1998; Whiteneck et al, 1999); mental factors such as depression (Kalpakjian et al, 2009) and emotional distress (Vissers et al, 2008); and environmental factors such as lack of transportation (Noreau et al, 1999), inaccessible physical environments (Packer et al, 2007), and inadequate social or familial support (Gorzkowski et al, 2011).…”
Section: Introductionmentioning
confidence: 99%